EVALUASI SISTEM INFORMASI RUMAH SAKIT UNTUK MENGETAHUI MINAT PENGGUNA DENGAN METODE UTAUT (Studi Kasus: RS. Jati Husada Karanganyar) - Rohmadi . (Politeknik Indonusa Surakarta, 2017)
Use of information technology is essential for the organization, because it can increase the effectiveness and efficiency of organizational performance. But the application of information technology is not always successful. One of the critical success factors of the application of information technology is the attitude of the users who use the technology, user attitude reflected the extent of interest in using the information system. This study aims to know the influence of performance expectancy, effort expectancy, social influence and facilitating conditions to the intentions of the user (behavioral intention). The model is a combination of eight models UTAUT user acceptance of technology that had been developed previously. Four constructs of UTAUT used as the determinant affecting the intentions of the user (behavioral intention). The fourth construct is moderated by variables of age and experience. Data obtained through 45 questionnaires distributed to a user purposive sampling hospital information system Jati Husada Karanganyar. The analysis showed that the only effort expectancy with strong ties to the behavioral intention, in others is quite strong. Moderation showed no effect on intention behavioral